Epidemiological study of traumatic brain injury in a tertiary care centre in South India - Asher, Prasanth; Joseph, Jijo Joseph; Pendro, Varun Singh; Peethambaran, Anilkumar; Prabhakar, Rajmohan Bhanu (International Surgery Journal, 2020)
Background: This study investigated the epidemiological pattern of traumatic brain injury (TBI) in our hospital, so as to juxtapose with available statistics and formulate recommendations for patient betterment. Methods: The Government Medical College, Thiruvananthapuram was the setting of this cross-sectional longitudinal study and included all patients admitted with clinical/radiological evidence of TBI over a period of three months (October 2019 to December 2019). Details regarding mechanism of injury and the socioeconomic background of the subjects were collected during the stay in hospital, by means of a semi structured questionnaire. SPSS software was used to analyze the data collected. Results: Out of 658 patients included in the study, majority of the subjects belonged to the age group 30-60 years. About 80% of subjects were males. 63% were manual laborers. Majority of the patients had about 10-15 days’ stay in the hospital. Road traffic accidents were the most common mechanism of injury and involved two wheelers mainly. Lack of helmet and restraining seat belt was noted in a sizeable percent of the subjects. Loss of consciousness was the most common complaint and GCS in the majority of subjects ranged from 9-13. Subdural hematomas and hemorrhagic contusions were the most common CT findings. 39.7% of the patients had associated spinal injury. About 48% of the subjects were operated. There was 7% mortality. Conclusions: Road traffic accidents accounted for the majority of traumatic brain injury incidents and a sizeable portion of patients required expert neurosurgical care.